Study of the electrochemical behaviors of ion-binding to calmodulin - Min CUI; Jujie REN; Junxin LI (Journal of Hebei University of Science and Technology, 2017)
In order to research the competitive binding with CaM between metal ions and Ca2+, electrochemical impedance spectroscopy (EIS) of ion (such as Ca2+,Cd2+,Al3+,Fe3+) -loaded CaM self-assembled membrane on Au electrode in 0.15 mol/L NaCl solution containing 2 mmol/L 3-/4- at pH 6.5 is investigated. The results indicate that the ion-binding property of CaM can be detected by the change of the electrochemical reaction resistance. Ca2+,Cd2+ and Al3+ can combine with CaM,and Fe3+ can’t combine with CaM. The binding ability of Ca2+ to CaM is stronger than that of Al3+. Ca2+ binding site of CaM is different from that of Al3+ and same as that of Cd2+. Electrochemical impedance spectroscopy provides a new method for the research of metal ions and CaM competition binding.